Highly Oriented Thin Films of 2D Ruddlesden‐Popper Hybrid Perovskite toward Superfast Response Photodetectors. Issue 39 (7th August 2019) - Han, Shiguo; Yao, Yunpeng; Liu, Xitao; Li, Bingxuan; Ji, Chengmin; Sun, Zhihua; Hong, Maochun; Luo, Junhua
Abstract: 2D hybrid perovskites have shown great promise in the photodetection field, due to their intriguing attributes stemming from unique structural architectures. However, the great majority of detectors based on this 2D system possess a relatively low response speed (≈ms), making it extremely urgent to develop new candidates for superfast photodetection. Here, a new organic–inorganic hybrid perovskite, (PA)2 (FA)Pb2 I7 (EFA, where PA is n ‐pentylaminium and FA is formamidine), which features the 2D Ruddlesden–Popper type perovskite framework that is composed of the corner‐sharing PbI6 octahedra is reported. Significantly, photodetectors fabricated on highly oriented thin films, which exhibit a perfect orientation parallel to 2D inorganic perovskite layers, exhibit a superfast response time up to ≈2.54 ns. To the best of the knowledge, this figure‐of‐merit catches up with that of the top‐ranking commercial materials, and sets a new record for 2D hybrid perovskite photodetectors. Moreover, extremely high photodetectivity (≈1.73 × 10 14 Jones, under an incident power intensity of ≈46 µW cm −2 ), considerable switching ratios (>10 3 ), and low dark current (≈10 pA) are also achieved in the detector, indicating its great potential for high‐efficiency photodetection. These results shed light on the possibilities to explore new 2D candidates for assembling future high‐performance optoelectronic devices. Abstract : A solution‐processed photodetector based on highly‐oriented Ruddlesden‐Popper type hybrid perovskite film exhibits an ultrafast response time of ≈2.54 ns, which is one of the record value figure‐of‐merits for two‐dimensional (2D) hybrid materials. This work paves a potential pathway to explore new 2D candidates for assembling high‐performance photodetectors.